3D screen printing technology enables fabrication of oral drug dosage forms with freely tailorable release profiles - Enke, Marcel; Schwarz, Nicolle; Gruschwitz, Franka; Winkler, Daniela; Hanf, Felix; Jescheck, Lisa; Seyferth, Stefan; Fischer, Dagmar; Schneeberger, Achim (International Journal of Pharmaceutics, 2023)
3D printing offers new opportunities to customize oral dosage forms of pharmaceuticals for different patient populations, improving patient safety, care, and compliance. Although several notable 3D print technologies have been developed, such as inkjet printing, powder-based printing, selective laser sintering (SLS) printing, and fused deposition modelling (FDM), among others, their capacity is often limited by the number of printing heads. 3D screen-printing (3DSP) is based on a classic flatbed screen printing that is widely used in industrial applications for technical applications. 3DSP can build up thousands of units per screen simultaneously, enabling mass customization of pharmaceuticals. Here, we use 3DSP to investigate two novel paste formulations: immediate-release (IR) and extended-release (ER) using Paracetamol (acetaminophen) as the active pharmaceutical ingredient (API). Both disk-shaped and donut-shaped tablets were fabricated using one or both pastes to design drug delivery systems (DDS) with tailored API release profiles. The size and mass of the produced tablets demonstrated high uniformity. Characterization of the tablets physical properties, such as breaking force (25–39 N) and friability (0.002–0.237%), adhering to Ph. Eur (10th edition). Finally, drug release tests with a phosphate buffer at pH 5.8 showed Paracetamol release depended on the IR- and ER paste materials and their respective compartment size of the composite DDS, which can be readily varied using 3DSP. This work further demonstrates the potential of 3DSP to manufacture complex oral dosage forms exhibiting custom release functionalities for mass production.
CRIS-Team Scopus Importer:2023-06-30
Keywords: 3D printing; 3D screen printing; Additive manufacturing; Controlled release; Drug delivery system; Extended-release; Immediate-release; Paracetamol

Application of a three-fluid nozzle for the preparation of amorphous solid dispersions - Corell, Carolina; Seyferth, Stefan; Fischer, Dagmar; Schiffter, Heiko A. (Drying Technology, 2023)
In this work, the manufacture of amorphous solid dispersions of poorly water-soluble carbamazepine using a laboratory spray drying setup with a three-fluid nozzle and two separate liquid feed solutions of (a) the active and (b) the polymeric excipient (copovidone or basic butylated methacrylate copolymer) was investigated and compared to a traditional two-fluid nozzle setup. Results show that particles with the desired drug content were manufactured using the three-fluid nozzle setup. Amorphous solid dispersion could be obtained up to a drug load of 50% (w/w) processing solutions with miscible solvents and copovidone as polymer. Higher active concentrations, the use of immiscible solvents or switching of the capillaries led to a substantial crystallization of carbamazepine as seen in XRD and DSC analysis. The polymorphic form IV of carbamazepine was formed in the presence of copovidone at high solid concentrations of the liquid feed.
CRIS-Team Scopus Importer:2023-03-03
Keywords: amorphous solid dispersions; crystallization; nozzle; solubility; Spray drying

Evaluation of plasma trace element and mineral status in children and adolescents with phenylketonuria using data from inductively-coupled-plasma atomic emission and mass spectrometric analysis - Knerr, Ina; Blessing, Holger; Seyferth, Stefan; Watling, R J; Chaudhri, Anwar (Annals of Nutrition and Metabolism, 2013)
Background: Phenylketonuria (PKU) is caused by a severe phenylalanine hydroxylase deficiency; the mainstay of treatment is a low-phenylalanine diet. A diet which is so restrictive is associated with a risk of nutritional deficiencies. We investigated plasma concentrations for 46 elements, including minerals and trace elements. Methods: We enrolled 20 children and adolescents with PKU and 20 matched controls. Multi-elementary quantification was carried out by solution-based inductively coupled plasma atomic emission spectroscopy (ICP-AES) and ICP mass spectrometry (ICP-MS). Results: With the exception of manganese and aluminium, no significant differences were found for element levels between PKU patients and controls. As a trend, manganese levels were lower in PKU patients than in control subjects (p < 0.05) but were within the reference range. There was a positive linear relationship between manganese and tyrosine levels in subjects with PKU (r = 0.2295, p < 0.05). If detectable, potentially toxic elements were only identified in ultra-trace quantities in plasma samples of either group; aluminium levels were found to be slightly higher in PKU subjects than in controls (p < 0.01). Conclusion: The combination of ICP-AES and ICP-MS data is a useful diagnostic tool for element quantification at a high analytical rate and for monitoring bio-element status, e.g. in patients on a restrictive diet. Copyright © 2013 S. Karger AG, Basel.

Extent and Effect of Covering Laryngeal Structures with Synthetic Laryngeal Mucus via Two Different Administration Techniques - Semmler, Marion; Lasar, Sarina; Kremer, Franziska; Reinwald, Laura; Wittig, Fiori; Peters, Gregor; Schraut, Tobias; Wendler, Olaf; Seyferth, Stefan; Schützenberger, Anne; Dürr, Stephan (Journal of Voice, 2023)
Objective: The first goal of this study was to investigate the coverage of laryngeal structures using two potential administration techniques for synthetic mucus: inhalation and lozenge ingestion. As a second research question, the study investigated the potential effects of these techniques on standardized voice assessment parameters. Methods: Fluorescein was added to throat lozenges and to an inhalation solution to visualize the coverage of laryngeal structures through blue light imaging. The study included 70 vocally healthy subjects. Fifty subjects underwent administration via lozenge ingestion and 20 subjects performed the inhalation process. For the first research question, the recordings from the blue light imaging system were categorized to compare the extent of coverage on individual laryngeal structures objectively. Secondly, a standardized voice evaluation protocol was performed before and after each administration to determine any measurable effects of typical voice parameters. Results: The administration via inhalation demonstrated complete coverage of all laryngeal structures, including the vocal folds, ventricular folds, and arytenoid cartilages, as visualized by the fluorescent dye. In contrast, the application of the lozenge predominantly covered the pharynx and laryngeal surface toward the aryepiglottic fold, but not the inferior structures. All in all, the comparison before and after administration showed no clear effect, although a minor deterioration of the acoustic signal was noted in the shimmer and cepstral peak prominence after the inhalation. Conclusions: Our findings indicate that the inhalation process is a more effective technique for covering deeper laryngeal structures such as the vocal folds and ventricular folds with synthetic mucus. This knowledge enables further in vivo studies on the role of laryngeal mucus in phonation in general, and how it can be substituted or supplemented for patients with reduced glandular activity as well as for heavy voice users.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Blue light imaging; Fluorescein; High-speed videoendoscopy; Inhalation; Lozenge; Synthetic mucus

Improved stability of polyclonal antibodies: A case study with lyophilization-conserved antibodies raised against epitopes from the malaria parasite Plasmodium falciparum - Simon, Nina; Sperber, Christine; Voigtländer, Cornelia; Born, Julia; Gilbert, Daniel; Seyferth, Stefan; Lee, Geoffrey; Kappes, Bärbel; Friedrich, Oliver (European Journal of Pharmaceutical Sciences, 2020)
Antibodies can be produced as polyclonal (pAb) or monoclonal (mAb) liquid formulations with limited shelf-life. For pAbs, unlike mAbs, only little is known about excipients and lyophilization affecting antibody stability upon reconstitution. We used a model pAb directed against Plasmodium falciparum (Pf) pyridoxal 5′-phosphate synthase 2 (Pdx2) to systemically study effects of bulking agents (amino acids, phosphate buffers, salt solutions), sugar(alcohols), surfactants and protein additions (bovine serum albumin, BSA) in liquid pAb formulations (isolated or in combinations) on the activity to detect the antigen in Pf extracts by Western blots. Repeated freeze-thaw cycles (20x) and extended room temperature storage markedly compromised pAb stability, the former being ameliorated by addition of cryoprotectants (glycerol, sucrose). Lyophilization of pure liquid pAb formulation markedly decreased antibody reactivity upon reconstitution which was not preserved by most bulking agents tested (e.g., histidine, arginine, acetate). Among the tested salt solutions (NaCl, Ringer, PBS), phosphate buffered saline had the largest lyoprotective potential, alongside sucrose, but not trehalose or maltitol. Among combinations of excipients, PBS, sucrose, low concentration BSA and Tween potently preserved PfPdx2 stability. Results for PBS were transferable to PfEnolase pAb, indicating that some of the formulations investigated here might be a low-cost solution for more general applicability to pAbs.
CRIS-Team Scopus Importer:2019-11-15

Kinetic, thermodynamic, and mechanistic patterns for free (unbound) cytochrome c at Au/SAM junctions: Impact of electronic coupling, hydrostatic pressure, and stabilizing/denaturing additives - Seyferth, Stefan; et al. (Chemistry - A European Journal, 2006)
Combined kinetic (electrochemical) and thermodynamic (calorimetric) investigations were performed for an unbound (intact native-like) cytochrome c (CytC) freely diffusing to and from gold electrodes modified by hydroxyl-terminated self-assembled monolayer films (SAMs), under a unique broad range of experimental conditions. Our approach included: 1) fine-tuning of the charge-transfer (CT) distance by using the extended set of Au-deposited hydroxyl-terminated alkanethiol SAMs [-S-(CH)-OH] of variable thickness (n = 2, 3, 4, 6, 11); 2) application of a high-pressure (up to 150MPa) kinetic strategy toward the representative Au/SAM/CytC assemblies (n = 3, 4, 6); 3) complementary electrochemical and microcalorimetric studies on the impact of some stabilizing and denaturing additives. We report for the first time a mechanistic changeover detected for "free" CytC by three independent kinetic methods, manifested through 1) the abrupt change in the dependence of the shape of the electron exchange standard rate constant (k ) versus the SAM thickness (resulting in a variation of estimated actual CT range within ca. 15 to 25 Å including ca. 11 Å of an "effective" heme-to-ω-hydroxyl distance). The corresponding values of the electronic coupling matrix element vary within the range from ca. 3 to 0.02cm ; 2) the change in activation volume from +6.7 (n = 3), to ≈ 0 (n=4), and -5.5 (n=6) cmmol (disclosing at n=3 a direct pressure effect on the protein's internal viscosity); 3) a "full" Kramerstype viscosity dependence for k at n = 2 and 3 (demonstrating control of an intraglobular friction through the external dynamic properties), and its gradual transformation to the viscosity independent (nonadiabatic) regime at n=6 and 11. Multilateral cross-testing of "free", CytC in a native-like, glucose-stabilized and urea-destabilized (molten-globule-like) states revealed novel intrinsic links between local/ global structural and functional characteristics. Importantly, our results on the high-pressure and solution-viscosity effects, together with matching literature data, strongly support the concept of "dynamic slaving", which implies that fluctuations involving "small" solution components control the proteins' intrinsic dynamics and function in a highly cooperative manner as far as CT processes under adiabatic conditions are concerned. © 2006 Wiley-VCH Verlag GmbH & Co. KGaA.

Measurement of shrinkage and cracking in lyophilized amorphous - Ullrich, Sabine; Seyferth, Stefan; Lee, Geoffrey (International Journal of Pharmaceutics, 2015)
UnivIS-Import:2015-10-26:Pub.2015.nat.dchph.lphte.measur_92
Keywords: Lyophilization; Shrinkage; Cracking; Freezing; Trehalose

Measurement of Shrinkage and Cracking in Lyophilized Amorphous Cakes, Part 3: Hydrophobic Vials and the Question of Adhesion - Ullrich, Sabine; Seyferth, Stefan; Lee, Geoffrey (Journal of Pharmaceutical Sciences, 2015)
The importance of cake adhesion to the inside vial wall during lyophilization of amorphous trehalose cakes was determined by using hydrophobized vials. The degrees of cake shrinkage and cracking were determined independently by photographic imaging of the cake top surface in a dark cell. Additionally, measurements with microcomputed tomography were performed. Adhesion is found to be a determining factor in both cake shrinkage and cracking. The correlation between cake detachment from the vial inner wall and trehalose concentration indicates that adhesion of the frozen solute phase is a determining factor in shrinkage. The hydrophobized vials give reduced cracking at trehalose concentrations of up to 15%. The reduced wetting of the hydrophobized inside vial wall gives a planar cake topography with a uniform distribution of cracks within the cake.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.lphte.measur_6
Keywords: lyophilization; amorphous; contact angles; materials science; excipients

Measurement of Shrinkage and Cracking in Lyophilized Amorphous Cakes. Part I: Final-Product Assessment - Ullrich, Sabine; Seyferth, Stefan; Lee, Geoffrey (Journal of Pharmaceutical Sciences, 2015)
An experimental technique is presented to determine independently shrinkage and cracking in lyophilized amorphous cakes based on photographic imaging of their top surface. An inverse correlation between cake shrinkage and cracking during freeze-drying is seen. Shrinkage relaxes the drying tension and gives little cracking, whereas if shrinkage is restrained then more cracking occurs. A lower shrinkage and greater cracking with higher disaccharide concentration correlates with change in cake hardness and brittleness. Adhesion of the cake to the inside vial wall could not be identified as a determining factor for shrinkage. Shrinkage is non-uniform across the cake's surface and is manifested largely in the peripheral region. A correlation between shrinkage and wg' for different disaccharides suggests that drying tension develops as non-frozen water is lost from the porous solid after sublimation of the ice phase has exposed the solid/gas interface.
UnivIS-Import:2015-03-09:Pub.2015.nat.dchph.lphte.measur
Keywords: Amorphous; Cracking; Freeze-drying; Lyophilization; Mechanical properties; Morphology; Shrinkage

Retronasal olfactory function in patients with smell loss but subjectively normal flavor perception - Liu, David Tianxiang; Besser, Gerold; Renner, Bertold; Seyferth, Stefan; Hummel, Thomas; Mueller, Christian Albert (Laryngoscope, 2019)
Objectives The human sense of smell constitutes the main part of flavor perception. Typically, patients with loss of olfactory function complain of diminished perception during eating and drinking. However, some patients with smell loss still report normal enjoyment of foods. The aim of the present study was to compare orthonasal and retronasal olfactory function in patients with non-sinonasal smell loss and subjectively normal flavor perception. Methods Nineteen patients (mean age [range] 52.0 [8-83 years]) with self-reported olfactory impairment but subjective normal flavor perception were included. Olfactory performance was assessed using the Sniffin' Sticks (TDI) for orthonasal and the Candy Smell Test (CST) for retronasal function. Visual analogue scales were used for self-assessment of odor (SOP), taste (STP), and flavor perception (SFP), ranging from 0 (no perception) to 10 (excellent perception). Results Mean (SD) SFP was 8.0 (1.8). Mean (SD) orthonasal TDI-score of all patients was 14.4 (5.3, range 6-25.3) with 11 patients classified as anosmic and eight as hyposmic. Mean/SD retronasal CST-score was 8.8 (2.7, range 3-13) within the range of anosmia/hyposmia. No correlation was found between SFP and the CST (P = .62). Conclusion The present results showed that despite claiming normal flavor perception, our patients were ortho- and retronasally dysosmic using standard tests for olfactory function. Although other explanations could be possible, we suggest that this subjective flavor perception might be due to unconscious memory recall from previously experienced cross-modal sensory interactions. Level of Evidence 4 Laryngoscope, 2019
CRIS-Team WoS Importer:2019-09-20

Scalable 3D Screen Printing Technology in Pharmaceutical Manufacturing - High Degree of Freedom in Terms of Drug Choice - Schneeberger, Achim; Seyferth, Stefan; Fischer, Dagmar (Archives of Dentistry, 2021)

Skin sodium is increased in male patients with multiple sclerosis and related animal models - Huhn, Konstantin; Linz, Peter; Pemsel, Franziska; Michalke, Bernhard; Seyferth, Stefan; Kopp, Christoph; Chaudri, Mohammad Anwar; Rothhammer, Veit; Dörfler, Arnd; Uder, Michael; Nagel, Armin M.; Müller, Dominik N.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Novel MRI techniques allow a noninvasive quantification of tissue sodium and reveal the skin as a prominent compartment of sodium storage in health and disease. Since multiple sclerosis (MS) immunopathology is initiated in the periphery and increased sodium concentrations induce proinflammatory immune cells, the skin represents a promising compartment linking high sodium concentrations and MS immunopathology. We used a 7-T sodium MRI (23Na-MRI) and inductively coupled plasma mass spectrometry to investigate the skin sodium content in two mouse models of MS. We additionally performed 3-T 23Na-MRI of calf skin and muscles in 29 male relapsing-remitting MS (RRMS) patients and 29 matched healthy controls. Demographic and clinical information was collected from interviews, and disease activity was assessed by expanded disability status scale scoring. 23Na-MRI and chemical analysis demonstrated a significantly increased sodium content in the skin during experimental autoimmune encephalomyelitis independent of active immunization. In male patients with RRMS, 23Na-MRI demonstrated a higher sodium signal in the area of the skin compared to age- and biological sex-matched healthy controls with higher sodium, predicting future disease activity in cranial MRI. In both studies, the sodium enrichment was specific to the skin, as we found no alterations of sodium signals in the muscle or other tissues. Our data add to the recently identified importance of the skin as a storage compartment of sodium and may further represent an important organ for future investigations on salt as a proinflammatory agent driving autoimmune neuroinflammation such as that in MS.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Experimental autoimmune encephalomyelitis; Multiple sclerosis; Skin; Sodium magnetic resonance imaging

Soluble CD83 improves and accelerates wound healing by the induction of pro-resolving macrophages - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; König, Christina; Wild, Andreas; Tauchi, Miyuki; Ostalecki, Christian; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, Sabine A.; Fuchs, Maximilian; et al. (Frontiers in Immunology, 2022)
To facilitate the recovery process of chronic and hard-to-heal wounds novel pro-resolving treatment options are urgently needed. We investigated the pro-regenerative properties of soluble CD83 (sCD83) on cutaneous wound healing, where sCD83 accelerated wound healing not only after systemic but also after topical application, which is of high therapeutic interest. Cytokine profile analyses revealed an initial upregulation of inflammatory mediators such as TNFα and IL-1β, followed by a switch towards pro-resolving factors, including YM-1 and IL-10, both expressed by tissue repair macrophages. These cells are known to mediate resolution of inflammation and stimulate wound healing processes by secretion of growth factors such as epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), which promote vascularization as well as fibroblast and keratinocyte differentiation. In conclusion, we have found strong wound healing capacities of sCD83 beyond the previously described role in transplantation and autoimmunity. This makes sCD83 a promising candidate for the treatment of chronic- and hard-to-heal wounds.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD83; macrophages; stem cells; therapy; tissue regeneration; wound healing

Soluble CD83 promotes cutaneous wound healing in an IDO-and beta-catenindependent manner - Royzman, Dmytro; Peckert-Maier, K.; Stich, L.; Wild, Andreas; Ostalecki, C.; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, S. A.; Berking, Carola; Zinser, Elisabeth; Steinkasserer, Alexander (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Structural studies of EDTA-induced fibrillation of salmon calcitonin - Seyferth, Stefan; Lee, Geoffrey (Pharmaceutical Research, 2003)

The soluble CD83 molecule accelerates wound closure and improves wound healing quality - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; Wild, Andreas; Ostalecki, Christian; Seyferth, Stefan; Eming, Sabine A.; Fuchs, Maximilian; Kunz, Meik; Sturmer, Ewa K.; Peters, Eva M. J.; Berking, Carola; et al. (WOUND REPAIR AND REGENERATION, 2022)
CRIS-Team WoS Importer:2022-09-16

The tangential flow absorption model (TFAM) - a novel dissolution method for evaluating the performance of amorphous solid dispersions of poorly water-soluble actives - Haering, Bastian; Seyferth, Stefan; Schiffter, Heiko A. (European Journal of Pharmaceutics and Biopharmaceutics, 2020)
There is a substantial demand for absorptive dissolution tests, as single vessel dissolution experiments were originally not designed for testing supersaturating systems. Current approaches suffer from inadequate mass transfer of the dissolved active from the dissolution site, discrepancies in the fluid volume compared to in vivo intestinal fluid volumes or the dilution of functional excipients. In this work a novel dissolution apparatus was developed that enables adjustable mass transfer of the active through a membrane, while retaining the functional polymeric excipients at the dissolution site. Using this setup the dissolution behavior of various spray dried amorphous solid dispersions containing carbamazepine, hydrochlorothiazide and ketoconazole as model actives at intermediate and high supersaturation levels was evaluated. Compared to non-absorptive dissolution experiments, differences in concentration-time profiles were noted. The experiments with a high supersaturation of ketoconazole revealed a concentration decrease over time under absorptive conditions. Additionally, it was observed that the difference between "spring" as well as "spring and parachute" formulations was less pronounced with increasing drug efflux. Further, the apparatus was also tested with Fasted State Simulated Intestinal Fluid as dissolution medium and results were compared to phosphate buffer pH6.8. As major benefits of the new TFAM apparatus the easy experimental procedure and sample preparation for drug concentration measurements using spectroscopy in the permeate, without the necessity for additional filtration and/or centrifugation to remove precipitated drug molecules, could be highlighted. This TFAM approach seems to be a promising tool for identifying formulations for amorphous solid dispersions with optimal in vitro performance.
CRIS-Team Scopus Importer:2020-07-10
Keywords: amorphous solid dispersions; crystallization inhibition; dissolution testing; polymers; poorly water-soluble actives; spray drying; tangential flow filtration

Topical systems for the controlled release of antineoplastic Drugs: Oxidized Alginate-Gelatin Hydrogel/Unilamellar vesicles - Stagnoli, Soledad; Garro, Cintia; Ertekin, Özlem; Heid, Susanne; Seyferth, Stefan; Soria, Gastón; Mariano Correa, N.; Leal-Egaña, Aldo; Boccaccini, Aldo R. (Journal of Colloid and Interface Science, 2023)
The efficacy of chemotherapeutic procedures relies on delivering proper concentrations of anti-cancer drugs in the tumor surroundings, so as to prevent potential side effects on healthy tissues. Novel drug carrier platforms should not just be able to deliver anticancer molecules, but also allow for adjustements in the way these drugs are administered to the patients. We developed a system for delivering water-insoluble drugs, based on the use of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), or bis(2-ethylhexyl) sulfosuccinate benzyl-n-hexadecyldimethylammonium (BHD-AOT), embedded into oxidized alginate-gelatin (ADA/Gel) hydrogel, emulating a patch for topic applications. After being loaded with curcumin, cancer cells such as human colorectal adenocarcinoma (HCT116 and DLD-1) and melanoma cell lines (MEL501), and non-malignant cells such as mammary epithelial cell lines (NMuMG) and embryonal fibroblasts (NIH 3T3 or NEO cells) were analyzed for biocompatibility and cytotoxic effects. The results show that the proposed system can load comparatively higher concentrations of the drug (with respect to other nano/microcarriers in the literature), and that it can enhance the likelihood of the drug being uptaken by cancer cells instead of non-malignant cells. These assays were complemented by diffusion studies across the stratum corneum of rat skin, with the aim of determining the system's efficiency during topical application. Finally, the stability of the patch was tested after lyophilization to determine its potential pharmaceutical use. As a whole, the combined system represents a highly reliable and robust method for embedding and delivering complex insoluble chemotherapeutical molecules, and it is less invasive than other alternative methods in the literature.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Controlled antineoplastic drug release; Hydrogel; Nanocarriers; Topical drug delivery system